DAMPAK USIA DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA JAKARTA UTARA - Zebua, Lydia Patricia; Viriany, Viriany (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to test whether there is an effect of age and sanctions on taxpayer compliance. The population in this study are people who already have taxes and work in North Jakarta. The number of samples in this study were 200 respondents. The sampling technique used purposive sampling method. The research method used is quantitative with data sources in the form of primary data. The results of this study provide empirical evidence that partially the variables of age independence and tax sanctions have a positive effect on audit quality. Simultaneously, the variables of age and tax sanctions have a significant effect on taxpayer compliance. Older respondents show a higher level of compliance, and tax sanctions play an important role in encouraging compliance. These findings have implications for tax policy, encouraging more effective tax socialization and education programs, as well as recommendations for increasing tax awareness among young taxpayers